1998
DOI: 10.1016/s0969-2126(98)00148-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and conformation of a DNA–RNA hybrid duplex with a polypurine RNA strand: d(TTCTTBr5CTTC)–r(GAAGAAGAA)

Abstract: . The present DNA-RNA hybrid duplex containing a polypurine RNA strand exhibits standard A-form geometry. This observation might suggest that the RNA PPT resists the RNase H activity of HIV reverse transcriptase as a result of its A-form conformation. In addition, there appears to be a correlation between the percentage purine content of the RNA and the DNA backbone conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…The A-form major groove width is reported to be small, ∼  3 − 6 Å (20,61). The size of hexahydrate Mg 2 + ions found inside the A-form major groove in the crystal structure is ∼ 8 Å (16), however, the authors postulate that facile exchange of coordinated water molecules is necessary to allow hydrated Mg 2 + ions to enter the groove without hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…The A-form major groove width is reported to be small, ∼  3 − 6 Å (20,61). The size of hexahydrate Mg 2 + ions found inside the A-form major groove in the crystal structure is ∼ 8 Å (16), however, the authors postulate that facile exchange of coordinated water molecules is necessary to allow hydrated Mg 2 + ions to enter the groove without hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…26,47,48 All of these sequences, r-( 5 0 g-a-a-g-a-g-a-a-g-c 3 0 ), r-( 5 0 g-a-a-g-a-a-g-a-g 3 0 ) and r-( 5 0 g-a-a-g-a-a-g-a-a 3 0 ), contain deformable a-g-a steps. The Conn et al 26 sequence crystallizes in the same space group, P2 1 2 1 2 1 , as the hybrid reported here; the other two crystallize in space group P6 1 .…”
Section: Structural Basis For Ppt Recognitionmentioning
confidence: 99%
“…Form I: The structure was solved by the molecular replacement method using the program package AMoRe (Navaza, 1994) with a nonamer DNA•RNA hybrid duplex (Xiong & Sundaralingam, 1998) as the search model+ Correctness of the structure was confirmed by peaks corresponding to the 29-hydroxyl groups absent from the model DNA strand and a clear indication of the bulged residue in the very first F o Ϫ F c difference Fourier map+ The trial structure was then refined using the program CNS (Brunger et al+, 1998)+ The nucleic acid parameter file dna-rna_rep+param (Parkinson et al+, 1996) was used with the dihedral angle restraint released for the bulged cytosine 39, 59-diphosphate+ Ten percent of the reflections were used for the calculation of R free (Brunger, 1992)+ Two metal ions with six and seven coordinating ligands involving water oxygens and phosphate oxygens were identified in the F o Ϫ F c and 3F o Ϫ 2F c electron density maps+ Although both Mg 2ϩ (annealing buffer) and Ca 2ϩ (crystallization buffer) ions were present in the crystallization mixture, the metals were identified as Ca 2ϩ ions based on their thermal factors and metal-ligand distances+ Because the Ca 2ϩ ion has an f0 equal to 1+286 at the Cu Ka wavelength, it provides a unique opportunity to verify its existence by anomalous difference Fourier+ The calcium locations were later confirmed by peaks at above 4s and 5s, respectively, in the anomalous difference Fourier map, calculated by using anom- (8) 1 + 3 1 + 3 alous differences in the Friedel pairs (DANO) as coefficients and phases calculated from the final structure model retarded by 908 (Phi_calc Ϫ 90)+ A total of 23 water molecules were included in the refinement that gave the final R work /R free of 20+4%/22+1% for 3,704 unique reflections (F . 2sF ) in the resolution range 10-2+2 Å+ Data and refinement statistics are summarized in Table 1+ The coordinates and the structure factors have been deposited in the Nucleic Acids Database (NDB) and the Protein DataBank (PDB) with access codes AR0026 and 1DQF, respectively+ Form II: The structure was obtained in the space group P4 3 2 1 2 by the molecular replacement method using the Form I structure as the search model with the bulged cytosine residue not included initially+ The refinement procedures were the same as above+ Despite a tenfold increase of Ca 2ϩ ion concentration used in the crystallization mixture compared to the Form I crystal, there was no calcium ions located in the structure+ The anomalous difference Fourier map was featureless, which confirmed the absence of the calcium ion+ The final structure included 57 water molecules with a R work /R free of 20+2%/24+3% for 6,022 unique reflections in the resolution range of 10-1+7 Å+ Refinement statistics are summarized in Table 1 and the coordinates and structure factors have been deposited in NDB and PDB with access codes AR0027 and 1DQH, respectively+…”
Section: Structure Solution and Refinementmentioning
confidence: 99%